PERSEPSI GURU DAN PUSTAKAWAN SLB NEGERI 1 SUNGAI PAGU TERHADAP DEPRIVASI INFORMASI BAGI SISWA TULI - Farid Hidayat (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2022)
This study aims to explain the views or perceptions of teachers and librarians as well as the responses of Deaf students at SLB Negeri 1 Sungai Pagu to the deprivation of information access. The type of this research is qualitative using descriptive method. Data was collected through observation, interviews, and questionnaires. These data were obtained from filling out questionnaires to six respondents at random and the results of interviews with school principals, librarians, teachers who had served as librarians, and six Deaf students from various levels. The results obtained are that some teachers at SLB Negeri 1 Sungai Pagu only understand this problem after receiving a simple explanation and in practice, the application of ethics to interacting with Deaf students is not optimal. In perception the librarian actually understands this problem, but she finds it difficult to overcome information deprivation because of the limited collection, access and facilities available in the library space. Based on the point of view of Deaf students, the lack of references to Deaf culture greatly impacts the low level of information absorption among Deaf students themselves.